2021
DOI: 10.1021/acs.inorgchem.1c02976
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reduction of Niobium(V) Species to Promote Molecular Niobium/Tantalum Separation

Abstract: The critical metals niobium (Nb) and tantalum (Ta) coexist in mineral sources, requiring a separation step to purify the elements from one another. The industrial separation process by solvent extraction uses stoichiometric hydrofluoric acid to manifest differences in the speciation of these otherwise chemically similar elements. The identification of alternative methods to separate Nb/Ta is desirable for fluoride waste reduction. In pursuit of this goal, the novel complexes [Na­(CH3CN)3(Et2O)]­[M­((S)-BINOLat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…0.75 V, allowing for the selective reduction and leaching of the Nb complex, resulting in a S Ta/Nb value of 6 ± 2. 34 This study demonstrated a proof-of-concept Ta/Nb separation procedure based on fundamental differences in bonding interactions in Ta versus Nb complexes.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…0.75 V, allowing for the selective reduction and leaching of the Nb complex, resulting in a S Ta/Nb value of 6 ± 2. 34 This study demonstrated a proof-of-concept Ta/Nb separation procedure based on fundamental differences in bonding interactions in Ta versus Nb complexes.…”
Section: Introductionmentioning
confidence: 87%
“…4-250. [19][20][21][22][23][24][25]34 However, it should be understood that this system is not yet industrially viable due to the air/moisture sensitivity of the compounds, the moderate to low yields of 1-M, and the high cost of the starting materials. Instead, this result should be viewed as a fundamental proof-of-concept separation demonstrating the viability of this novel separation strategy.…”
Section: Demonstration Of Ta/nb Separationmentioning
confidence: 99%
“…The dedication of our method to obtaining ultrapure reagents on a small scale also justifies the use of small amounts of HF, not recommended for safety reasons, whose presence provides such an excellent separation effect. It should be mentioned that in the recent literature, fluoride systems for the separation of Nb and Ta are still eagerly used [40,45], although gradually one can find attempts to eliminate the use of fluoride systems for the separation of Nb and Ta in oxalate [46,47] or phosphate [48] or electrochemical [49] systems, which is certainly a very good direction for large-scale industrial separation of these elements.…”
Section: Separation Of Tantalum From Niobium Using Fixed-bed Columnmentioning
confidence: 99%
“…There have been reports of different reactivities of Nb­(V) and Ta­(V) compounds. Our search of the literature, including the 1904–2013 annual reviews on niobium and tantalum chemistry by the Royal Society of Chemistry, shows that the reduction of Nb­(V) complexes to Nb­(IV) species is more likely than their Ta­(V) analogues, which is a major difference between the Nb­(V) and Ta­(V) chemistries. Bradley and Thomas have reported several reactions between MCl 5 [M = Nb­(V); Ta­(V)] and LiNR 2 (R = Me, Et, n Pr, n Bu). , As the alkyl chains increase, the extent of Nb­(V) to Nb­(IV) reduction increases in the products, while tantalum complexes remains at Ta­(V).…”
Section: Introductionmentioning
confidence: 99%
“…Upon heating Ta­(O 2 CNEt 2 ) 5 , in contrast, it remains in the V oxidation state. Studies of [Na­(CH 3 CN) 3 (Et 2 O)]­[M­(( S )-BINOLate) 3 ] [M = Nb, Ta; BINOL = ( S )-(−)-1,1′-bis­(2-naphthol)] have shown selective Nb­(V) reduction, while the Ta­(V) analogue exhibits no such reduction, as Furigay, Schatz, Schelter, and co-workers have recently reported . There are relatively few reports of different reactivities of Nb­(V) and Ta­(V) compounds while preserving the V oxidation state. , Muetterties and Wright have reported that isostructural, eight-coordinate Nb and Ta complexes [M­(tropolonate) 4 ] + Cl – show significant differences to hydrolysis .…”
Section: Introductionmentioning
confidence: 99%